RANCANG BANGUN SISTEM ADMINISTRASI DATA RAPID TEST BERBASIS WEB MENGGUNAKAN PHP DAN MySQL (STUDI KASUS : KLINIK PAPUA MEDIKA): Design and Build a Web-Based Rapid Test Data Administration System Using PHP and MySQL (Case Study: Papua Medika Clinic) - Prasetya Dwi Syahputra; Julius Panda Putra Naibaho; Fridolin F. Paiki (Universitas Papua, 2022)
The Rapid test data administration system at the Papua Medika Clinic which is still offline is a reference for creating titles that can be submitted to lecturers. Data input and data storage of patients who perform rapid test examinations are only carried out in Microsoft Excel, and the storage of daily rapid test results is combined. In addition, the data stored in Microsoft Excel is still based offline, as a consequence the admin who works is difficult to match and view patient data if the computer condition is being updated, temporary loss of electricity, viruses, and various kinds of disturbances on other computer devices. To overcome these problems, it is necessary to design a web-based Rapid Test data administration system to assist admins in managing patient data, as well as reports. Furthermore, the Rapid Test data administration system was built using the PHP programming language and MySQL Database Management System (DBMS). With this Administration system, the process of managing data, and printing results to patients is faster and more efficient.